2022
DOI: 10.21776/ub.agrise.2022.022.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Experience Shocks of Strategic Food Consumers in Indonesia During Covid-19 Pandemic

Abstract: COVID-19's negative externalities disrupted the supply of several commodities. Meanwhile, to combat the spread of COVID-19, various countries have implemented a lockdown policy, which impacts the economy's balance. Consumers' risks are increasing due to economic changes caused by the COVID-19 pandemic, which affects the higher level of volatility of various agricultural commodities in Indonesia, particularly strategic commodities. Thus, this research was designed to examine the experience shock of strategic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The result was that the short-term wholesale prices doubled due to supply constraints, although consumers suffered less, with official sources indicating that retail prices also increased on average by only 10% in Canada and 30% in the USA (Weersink et al 2021, p. 3). Undoubtedly, price volatility for staple commodities increased significantly as a direct result of the pandemic (Laili et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was that the short-term wholesale prices doubled due to supply constraints, although consumers suffered less, with official sources indicating that retail prices also increased on average by only 10% in Canada and 30% in the USA (Weersink et al 2021, p. 3). Undoubtedly, price volatility for staple commodities increased significantly as a direct result of the pandemic (Laili et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Eight commodities/foodstuffs were selected for this study, based on their consumption and contribution to inflation, as identified by the National Strategic Food Price Information Center and as employed in previous studies (Laksono and Yuliawati 2021;Laili et al 2022;Nurdjannah et al 2014). Table 1 provides information on each.…”
Section: Methodsmentioning
confidence: 99%
“…This condition can be attributed to various factors, such as changes in supply and demand, weather conditions, market speculation, and the economy. The list of commodities, such as rice, corn, chicken meat, broiler eggs, shallots, sugar, garlic, cayenne pepper, meat, red chili, and cooking oil represents a range of essential food items, each with its unique set of influencing factors [ 36 ]. Weather events, diseases, supply disruptions, and other factors have been reported to have cascading effects on crop yields and availability, leading to shortages and price increases.…”
Section: Introductionmentioning
confidence: 99%